Case Report: Off-Label Liraglutide Use in Children With Wolfram Syndrome Type 1: Extensive Characterization of Four Patients - Frontino, Giulio; Raouf, Tara; Canarutto, Daniele; Tirelli, Eva; Di Tonno, Raffaella; Rigamonti, Andrea; Cascavilla, Maria Lucia; Baldoli, Cristina; Scotti, Roberta; Leocani, Letizia; Huang, Su-Chun; Meschi, Franco; et al. (Frontiers in Pediatrics, 2021)
Aims: Wolfram syndrome type 1 is a rare recessive monogenic form of insulin-dependent diabetes mellitus with progressive neurodegeneration, poor prognosis, and no cure. Based on preclinical evidence we hypothesized that liraglutide, a glucagon-like peptide-1 receptor agonist, may be repurposed for the off-label treatment of Wolfram Syndrome type 1. We initiated an off-label treatment to investigate the safety, tolerability, and efficacy of liraglutide in pediatric patients with Wolfram Syndrome type 1. Methods: Pediatric patients with genetically confirmed Wolfram Syndrome type 1 were offered off-label treatment approved by The Regional Network Coordination Center for Rare Diseases, Pharmacological Research IRCCS Mario Negri, and the internal ethics committee. Four patients were enrolled; none refused nor were excluded or lost during follow-up. Liraglutide was administered as a daily subcutaneous injection. Starting dose was 0.3 mg/day. The dose was progressively increased as tolerated, up to the maximum dose of 1.8 mg/day. The primary outcome was evaluating the safety, tolerability, and efficacy of liraglutide in Wolfram Syndrome type 1 patients. Secondary endpoints were stabilization or improvement of C-peptide secretion as assessed by the mixed meal tolerance test. Exploratory endpoints were stabilization of neurological and neuro-ophthalmological degeneration, assessed by optical coherence tomography, electroretinogram, visual evoked potentials, and magnetic resonance imaging. Results: Four patients aged between 10 and 14 years at baseline were treated with liraglutide for 8-27 months. Liraglutide was well tolerated: all patients reached and maintained the maximum dose, and none withdrew from the study. Only minor transient gastrointestinal symptoms were reported. No alterations in pancreatic enzymes, calcitonin, or thyroid hormones were observed. At the latest follow-up, the C-peptide area under the curve ranged from 81 to 171% of baseline. Time in range improved in two patients. Neuro-ophthalmological and neurophysiological disease parameters remained stable at the latest follow-up. Conclusions: We report preliminary data on the safety, tolerability, and efficacy of liraglutide in four pediatric patients with Wolfram Syndrome type 1. The apparent benefits both in terms of residual C-peptide secretion and neuro-ophthalmological disease progression warrant further studies on the repurposing of glucagon-like peptide-1 receptor agonists as disease-modifying agents for Wolfram Syndrome type 1.